Conceptual model for the development of geo-ecological atlas of the natural reserve fund of Ukraine - Bondarenko, Eduard; Kyryliuk, Mykola (Geodesy and Cartography, 2023)
The article substantiates that the most complete cartographic model, which comprehensively characterizes the objects and territories of the natural reserve fund (NRF) of Ukraine is the geo-ecological atlas. It is indicated that the basis for the creation of the atlas is its conceptual model, within the framework of the formulation of its provisions are defined: the object of modeling, structure and composition of the modeled system, the characteristics of its elements, as well as inherent in the system cause-effect relationships that are considered essential to achieve the purpose of modeling. The functions of the atlas of NRF are formulated. The formal features of its content are interconnected. The authors in the context of the formulation and use of methodological principles of atlas completing with maps (sequential-traditional; block-issue; combined) applied combined principle and determined the optimal thematic content of the atlas in the form of a list of maps, grouped by sections and blocks (three sections, each of which contains two blocks of maps). The types of maps included in each section / block are defined (mainly they are: analytical (inventory), analytical-synthetic (evaluation), synthetic (recommendation, forecast), for each of which the indicators of mapping and methods of cartographic representation are justified.